Análisis jurídico sobre la aplicación de la corresponsabilidad parental en las resoluciones judiciales en los juicios de alimentos en la ciudad de Zamura durante el año 2012. - Orellana Feijóo, Jose Rodrigo (2013)
The present work contains the reality that food people live in the food trials, since they are being violated their rights, as is the correct application of parental responsibility enshrined in Art. 100 of the Children and Adolescents Code.